2019
DOI: 10.3389/fpsyg.2019.01858
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Expressed Humility for Non-humble Leaders: A Conservation of Resources Perspective

Abstract: Although existing studies to date predominately focus on the beneficial effects of leader expressed humility on followers, knowledge about how those behaviors impact the leaders themselves is scarce. Drawing on the conservation of resources theory, we develop and test a model that specifies for whom and how expressing humility has detrimental effects on leaders’ emotional exhaustion and the downstream implications of this effect for leaders’ turnover intentions and work-to-family conflict. Data from a multisou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…An example item is “I wouldn’t pretend to like someone just to get that person to do favors for me.” All items were rated on a seven‐point scale (1 = strongly disagree , 7 = strongly agree ). The Chinese version of the Honesty–Humility subscale has been showed good reliability in Chinese participants (Yang, Zhou, Wang, Lin & Luo, 2019). In this study, the index of CFA showed that this scale had an acceptable goodness of fit: χ 2 /df = 2.94, RMSEA = 0.06, CFI = 0.94, NFI = 0.94, GFI = 0.98.…”
Section: Methodsmentioning
confidence: 99%
“…An example item is “I wouldn’t pretend to like someone just to get that person to do favors for me.” All items were rated on a seven‐point scale (1 = strongly disagree , 7 = strongly agree ). The Chinese version of the Honesty–Humility subscale has been showed good reliability in Chinese participants (Yang, Zhou, Wang, Lin & Luo, 2019). In this study, the index of CFA showed that this scale had an acceptable goodness of fit: χ 2 /df = 2.94, RMSEA = 0.06, CFI = 0.94, NFI = 0.94, GFI = 0.98.…”
Section: Methodsmentioning
confidence: 99%
“…By applying the underlying logic of conservation of resources theory, Ma et al (2019) find that humble leaders act as energizers that increase followers' relational energy and consequently give rise to followers' constructive voice behavior. Interestingly, Yang, Zhou, et al (2019b) used this theory to examine the effect that humility has on the leader themselves and found that expressed humility served as a vehicle of leader emotional exhaustion (i.e., depleting a resource), leading to adverse downstream effects as turnover and work–family tension.…”
Section: Humble Leadership Theories and Nomological Netmentioning
confidence: 99%
“…In contrast to the overwhelmingly positive effects of humble leadership for followers, teams, and organizations, prior literature reveals mixed results regarding its impact on the leaders themselves. Yang, Zhou, et al (2019b) found that humble leadership can be exhausting and positively relates to leader work–family conflict and turnover intentions. Further, Zapata and Hayes‐Jones (2019) found that humble leadership made leaders seem less agentic but more communal.…”
Section: Humble Leadership Theories and Nomological Netmentioning
confidence: 99%
“…Studies demonstrate that it is likely to be inconsistent between individuals’ inner motivation and externally displayed behaviors ( Wright et al, 2018 ; Bharanitharan et al, 2020 ). Leaders can express humility instrumentally to reach desired goals without actually being humble ( Yang et al, 2019 ). Because of behaviors exhibited by authentic and pseudo leaders may be similar, researchers suggest the leader’s manipulative intentions (the degree of words and actions motivated by self-interest) are vital in distinguishing them ( Dasborough and Ashkanasy, 2002 ; Lin et al, 2017 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…As leader-expressed humility is measured behaviorally, research focuses on a pattern of displayed behaviors that emerges in interpersonal interactions and is readily apparent to others ( Owens et al, 2013 ). It is difficult to determine whether a person really has an inner state of motivation only by displayed behaviors ( Wright et al, 2018 ), a non-humble leader can counterdispositionally express humility to reach desired goals without actually being humble ( Yang et al, 2019 ). We suggest that employees are likely to assess leader-expressed humility as either genuine or hypocritical.…”
Section: Introductionmentioning
confidence: 99%